2016
DOI: 10.1038/leu.2016.174
|View full text |Cite|
|
Sign up to set email alerts
|

Principal component analysis uncovers cytomegalovirus-associated NK cell activation in Ph+ leukemia patients treated with dasatinib

Abstract: Dasatinib treatment markedly increases the number of large granular lymphocytes (LGLs) in a proportion of Ph leukemia patients, which associates with a better prognosis. The lymphocytosis is predominantly observed in cytomegalovirus (CMV)-seropositive patients, yet detectable CMV reactivation exists only in a small fraction of patients. Thus, etiology of the lymphocytosis still remains unclear. Here, we identified NK cells as the dominant LGLs expanding in dasatinib-treated patients, and applied principal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…We consider that this discrepancy can be explained by differential influences of dasatinib treatment on NK cell subsets. In contrast to dysfunctional CD56 neg NK cells, functionality of CD56 dim NK cells, which expanded in good correlation with CD56 neg NK cells in CMV + DA patients, is enhanced during dasatinib treatment, as we have shown previously 4. CD56 neg NK cells constitute only a minor subset in the total population of NK cells, even in CMV + DA patients with an increased number of CD56 neg NK cells.Thus, we assume that the major CD56 dim NK cell subset plays an important role in contributing to anti-leukemia effects, bringing about a better clinical response in CMV + DA patients.Despite the above mentioned, CD56 neg NK cell can be a predictive biomarker for therapeutic responses in DA patients.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…We consider that this discrepancy can be explained by differential influences of dasatinib treatment on NK cell subsets. In contrast to dysfunctional CD56 neg NK cells, functionality of CD56 dim NK cells, which expanded in good correlation with CD56 neg NK cells in CMV + DA patients, is enhanced during dasatinib treatment, as we have shown previously 4. CD56 neg NK cells constitute only a minor subset in the total population of NK cells, even in CMV + DA patients with an increased number of CD56 neg NK cells.Thus, we assume that the major CD56 dim NK cell subset plays an important role in contributing to anti-leukemia effects, bringing about a better clinical response in CMV + DA patients.Despite the above mentioned, CD56 neg NK cell can be a predictive biomarker for therapeutic responses in DA patients.…”
supporting
confidence: 76%
“…1,2 We and others have shown that dasatinib-induced expansion of CD8 + T cells and NK cells most likely involves CMV reactivation. 3,4 In our previous study, we applied PCA to a dataset of a wide range of NK cell markers to quantify the degree of CMV reactivation-driven NK cell differentiation. By this method, we showed that progressive NK cell differentiation induced by chronic NK cell activation through CMV reactivation occurred in CMV-seropositive (CMV + ) patients exclusively during dasatinib treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, lymphocytosis was found to have developed in 34.8% of the patients. The incidence of lymphocyte predominance in CML‐CP patients may depend on the history of cytomegalovirus (CMV) infection . Although the frequency of CMV‐positive patients was not determined in the present study, that of blood donors in Japan was reported to be 80% among patients in their 40s, 90% among those in their 50s and nearly 100% among those in their 60s …”
Section: Discussionmentioning
confidence: 60%
“…CD8 + T-cell expansions have also been reported in patients undergoing treatment with the promiscuous tyrosine kinase inhibitor dasatinib, which is licensed as a first line therapeutic option in the management of chronic myelogenous leukemia (CML) and Philadelphia chromosome-positive (Ph + ) acute lymphoblastic leukemia (ALL) 11 16 . In some cases, these expanded CD8 + T-cells can even mimic T-cell large granular lymphocytes (T-LGLs).…”
Section: Introductionmentioning
confidence: 99%